The influence of the time of antidotal treatment administration on its effectiveness against tabun-induced poisoning in mice - Kassa, Jirí (Acta medica (Hradec Kralove), 2004)
1. The influence of the time of administration of antidotal treatment consisting of anticholinergic drug (atropine) and oxime (pralidoxime, obidoxime, HI-6 or trimedoxime) on its effectiveness to eliminate tabun-induced lethal effects was studied in mice. 2. The therapeutic efficacy of antidotal treatment of tabun-induced acute poisoning depends on the time of its administration when obidoxime or the oxime HI-6 was used as an acetylcholinesterase reactivator. 3. Pralidoxime is practically ineffective to eliminate acute toxic effects of tabun regardless of the time of its administration. 4. Our results show that trimedoxime seems to be the most effective to eliminate lethal effects of tabun. In addition, its efficacy does not decrease when it is administered 5 min after tabun poisoning. 5. The findings support the hypothesis that trimedoxime appears to be the most suitable oxime to counteract acute toxicity of tabun because of its ability to eliminate lethal effects of tabun when it is injected 5 min after tabun challenge on the contrary to other oximes tested.
Keywords: oximy; Organophosphates; antidota; Organophosphate Poisoning; Oximes; chemické bojové látky; výsledek terapie; otrava organofosfáty; zvířata; myši; Poisoning; časové faktory; cholinesterasové inhibitory; Mice; organofosfáty; Male; Atropine; atropin; Treatment Outcome; reaktivátory cholinesterasy; Cholinesterase Reactivators; otrava; Animals; Chemical Warfare Agents; mužské pohlaví; Time Factors; Cholinesterase Inhibitors; Antidotes